فاعلية استخدام إستراتيجية الحلقات العلمية في التحصيل وتنمية الذكاء الاجتماعي لدى طالبات الصف السابع الأساس في مادة العلوم - طيب, م.شادمان أيوب (Sulaimani Journal for Humanities, 2023)
The research aims to identify the Effectiveness of the Scientific circles strategy in the achievement and its role in raising the Social intelligence of the seventh Basic class students in science. To achieve such a goal, the researcher put three null hypotheses. The research involved the seventh basic class students during the study year (2022 – 2023) in the (khake lewa) School. The researched adopted the experimental design of case-control study, with both pre and post-testing for achievement awareness variables. However, the research sample included (60) students randomly distributed in tow groups: an experimental group of (30) students studied science according to the Scientific circles strategy, and a control group composed of (30) students studied science by the conventional method. The researcher took in consideration the equivalence of both groups in a variable such as the (age, intelligence quotient and Social intelligence). The researcher prepared a test of achievement contain (51) question items characterized by validity and reliability, in order to obtain the item difficulty and discrimination indices and to evaluate the effectiveness of the wrong alternative. Likewise, the researcher used social intelligent contain (35) items characterized by validity and reliability. The researcher adapted (34) study plans: half by Scientific circles strategy and half by the conventional method. The researcher started on (25sep. 2022) and ended by (1 nov. 2022), during which the teacher gave lessons to both study groups. By completion of the research, application of research tool, data collection, and statistical analysis, the following results were obtainer: 1. Existing a difference between the averages for the mark in the two groups to the achievement, the result favor for the experimental group. 2. Existing a difference between the averages for the mark in the experimental group of pre-test and post-test in the creativity Social intelligence, the result benefit for the post –test. 3. Existing a difference between the averages for the mark in the two groups to the Social intelligence, the result favor for the experimental group.